The Relationship between Knowledge and Attitudes about Maintaining Genital Hygiene and the Incidence of Fluor Albus in Young Girls at SMA Negeri 1 Purwakarta, Purwakarta Regency, Indonesia - Ruciah, Ruciah (HM Publisher, 2023)
Proper knowledge and attitudes regarding genital hygiene can help young women maintain overall reproductive health. This is because proper hygiene practices can also protect the genital area from infections and other disorders, as well as promote general health and comfort. This study aimed to determine the relationship between knowledge and attitudes about maintaining genital hygiene with the incidence of fluor albus in adolescent girls at SMA Negeri 1 Purwakarta, Purwakarta Regency, Indonesia. This study is an analytical observational research with a cross-sectional approach. This study uses primary data obtained from the research subject interview process. A total of 211 research subjects took part in this study. In conclusion, no relationship between knowledge and attitudes about maintaining genital hygiene and the incidence of vaginal discharge in adolescent girls at SMA Negeri 1 Purwakarta, Purwakarta Regency, Indonesia.